If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3(x + 5) + 6 = 2x + 21 Reorder the terms: 2x + -3(5 + x) + 6 = 2x + 21 2x + (5 * -3 + x * -3) + 6 = 2x + 21 2x + (-15 + -3x) + 6 = 2x + 21 Reorder the terms: -15 + 6 + 2x + -3x = 2x + 21 Combine like terms: -15 + 6 = -9 -9 + 2x + -3x = 2x + 21 Combine like terms: 2x + -3x = -1x -9 + -1x = 2x + 21 Reorder the terms: -9 + -1x = 21 + 2x Solving -9 + -1x = 21 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -9 + -1x + -2x = 21 + 2x + -2x Combine like terms: -1x + -2x = -3x -9 + -3x = 21 + 2x + -2x Combine like terms: 2x + -2x = 0 -9 + -3x = 21 + 0 -9 + -3x = 21 Add '9' to each side of the equation. -9 + 9 + -3x = 21 + 9 Combine like terms: -9 + 9 = 0 0 + -3x = 21 + 9 -3x = 21 + 9 Combine like terms: 21 + 9 = 30 -3x = 30 Divide each side by '-3'. x = -10 Simplifying x = -10
| 225x^2=17 | | xy-6x=0 | | 3(6m-2)-8=9 | | 12x^2=2352 | | (2+15)=2x | | 2(x-7)+3+7=x+9 | | 3x*2=12 | | 9x+1=(7x-2)+(3x+7) | | 7x^2=2268 | | 44.13+.10x=80 | | 8(z+69)=48(z+4) | | 15x^2=4335 | | 38.86+0.50x=130 | | -2=0.25a-13 | | 3(x-5)-2(x+1)=15 | | 5(2y+3)-3y=-2(4y+1)-13 | | 3.25x=6+2.5x | | .25t+8=3 | | m^4-6m^3+6m^3-6m^2+6m-6=0 | | x-7y=8 | | 2(x-96)=14(x-6) | | 14x-4(x+7)=35 | | K^2X^2-KX-6=0 | | 44-(3c+4)=4(c+6)+c | | q-t=q+bx | | 22+4.1=2+32.6 | | 114r-95s+57= | | 2(x-5)=15 | | 4ax^2=0 | | 27-2x=45-x | | 3x-2(2.5)=19.5 | | 12=0.2x-11 |